Proceedings of the 49th Annual ACM SIGACT Symposium on Theory of Computing 2017
DOI: 10.1145/3055399.3055442
|View full text |Cite
|
Sign up to set email alerts
|

Randomized polynomial time identity testing for noncommutative circuits

Abstract: In this paper we show that the black-box polynomial identity testing for noncommutative polynomials f ∈ F z 1 , z 2 , · · · , z n of degree D and sparsity t, can be done in randomized poly(n, log t, log D) time. As a consequence, if the black-box contains a circuit C of size s computing f ∈ F z 1 , z 2 , · · · , z n which has at most t non-zero monomials, then the identity testing can be done by a randomized algorithm with running time polynomial in s and n and log t. This makes significant progress on a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Now, we can design small nondeterministic substitution automata that can nondeterministically effect this transformation from P i to P i,I for each i. guess the locations in I. The rest of the proof is similar to the proof of Theorem 2 in [AMR16].…”
Section: White-box Algorithm For +-Regular Circuitsmentioning
confidence: 92%
See 3 more Smart Citations
“…Now, we can design small nondeterministic substitution automata that can nondeterministically effect this transformation from P i to P i,I for each i. guess the locations in I. The rest of the proof is similar to the proof of Theorem 2 in [AMR16].…”
Section: White-box Algorithm For +-Regular Circuitsmentioning
confidence: 92%
“…Specifically, C may compute a nonzero exponential degree noncommutative polynomial, but it is not clear if we can test that by evaluating C on matrices of polynomial dimension. Also, the black-box PIT result of [AMR16] cannot be applied here since C can compute polynomials of double-exponential sparsity.…”
Section: Proof Of Claimmentioning
confidence: 99%
See 2 more Smart Citations
“…The Amitsur-Levitzki theorem states that a nonzero noncommutative polynomial p ∈ F X of degree < 2k cannot be an identity for the matrix ring M k (F). Additionally, it is shown that a nonzero noncommutative polynomial does not vanish on matrices of dimension logarithmic in the sparsity of the polynomial, yielding a randomized polynomial time algorithm for noncommutative circuits computing a nonzero polynomial of exponential degree and exponential sparsity [AJMR17].…”
Section: Introductionmentioning
confidence: 99%